Empowering migrant workers: the development and impact of the e-law consult application - Dian Ratu Ayu Uswatun Khasanah; Ronald Jolly Pongantung; Eko Andy Purnomo (Clío, 2025)
This study will create and test the e-Law Consult app, which helps Indonesian migrant workers understand and exercise their legal rights overseas, particularly women. The research uses the 4D development approach (Define, Design, Develop, and Disseminate) to design, build, and test the app. A needs analysis involving migrant worker surveys and interviews preceded app development and usability testing. Questionnaires, user comments, and case study analysis collected quantitative and qualitative data. The results show that the e-Law Consult software improves migrant workers' legal literacy and promotes women's rights abroad. Users may quickly get legal advice with the app. The conversation discusses how digital platforms empower migrant workers legally and the app's potential for scalability and acceptance in different countries. This study shows how technology can protect migrant workers and raise their legal understanding. Implications include better legal resources for migrant workers and legislative proposals to integrate technology into protection systems. This study contributes to knowledge by demonstrating its uniqueness, innovative use of technology, and practical solutions to migratory worker issues. This research could influence professional practices and global migrant worker protection regulations, making it valuable.